Ecological engineering in pond aquaculture: a review from the whole‐process perspective in China. (17th November 2020) - Liu, XingGuo; Shao, Zhengyi; Cheng, Guofeng; Lu, Shimin; Gu, Zhaojun; Zhu, Hao; Shen, Hongye; Wang, Jie; Chen, Xiaolong
Abstract: Pond aquaculture undeniably offers the potential for food production worldwide. In China, 45.83% of aquatic production is currently from pond aquaculture. However, with the continuous expansion of this practice, environmental problems such as a high level of water consumption, aquaculture water deterioration, pollution from effluent and aquatic product quality decline seriously restrict the sustainable development of pond aquaculture. In this review, we summarise the (i) the impacts of pond aquaculture on the environment, (ii) research progress in pond aquaculture ecological engineering, (iii) existing technologies regarding pond aquaculture ecological engineering systems, (iv) effects of applying pond aquaculture ecological engineering and (v) summary and prospects. Moreover, we discuss the merits and drawbacks of each method and technology, and future research priorities are reviewed. With this, an understanding of the role played by ecological engineering in pond aquaculture is provided, as well as guidance for precisely managing aquaculture water and effluent, aquaculture practices, and technological developments. In summary, the pond aquaculture ecological engineering can be managed so as to improve animal welfare and the stability of water treatment systems, reducing the adverse effects on the environment and public health, and enabling the sustainable development of pond aquaculture.